Effect of methionine sulfoxide on the synthesis and purification of aggregation-prone peptides - Reusche, Vanessa; Thomas, Franziska (ChemBioChem, 2021)
A two-step synthesis for methionine-containing hydrophobic and/or aggregation-prone peptides is presented that takes advantage of the reversibility of methionine oxidation. The use of polar methionine sulfoxide as a building block in solid-phase peptide synthesis improves the synthesis quality and yields the crude peptide, with significantly improved solubility compared to the reduced species. This facilitates the otherwise often laborious peptide purification by high-performance liquid chromatography. The subsequent reduction proceeds quantitatively. This approach has been optimised with the methionine-rich Tar-DNA-binding protein 43 (307-347), but is also more generally applicable, as demonstrated by the syntheses of human calcitonin and two aggregation-prone peptides from the human prion protein.
Gesehen am 18.04.2023